Inactivation of Lipopolysaccharide-Biosynthesizing Genes Altered Lipids Composition and Intensity in Cronobacter sakazakii - Xiaoqing Hu; Xi Yang; Shuyan Wu; Xuan Lu; Yuan Ma; Ziyi Tang; Xiaoyuan Wang; Xiaodong Huang; Shuiping Wang (Pathogens)
Gram-negative bacteria possess an asymmetric outer membrane, where the outer leaflet consists of LPSs and the inner leaflet comprises phospholipids. Cronobacter sakazakii, an opportunistic milk-borne pathogen that causes severe neonatal meningitis and bacteremia, displays diverse lipopolysaccharide (LPS) structures. As a barrier of the bacterial cell, LPSs likely influenced C. sakazakii resistance to environment stresses; however, there are no research reports on this aspect, hindering the development of novel bactericidal strategies overcoming the pathogen’s resilience. In the present study, therefore, C. sakazakii BAA894 and two LPS mutants (ΔlpxM and ΔwaaC) were employed to investigate its influences. The ΔwaaC mutant showed lower resistance to acidic, alkali, oxidative, and osmotic stresses compared to the wild-type strain BAA894, and the ΔlpxM mutant exhibited lower desiccation resistance but higher osmotic resistance. To uncover potential reasons for these differences, comparative lipidomics was conducted. The results showed that compared to BAA894, both mutants showed drastic changes in lipid quantity, and many changed lipids were unsaturated. Additionally, eleven lipid classes exhibited significant variation in the relative content. In particular, the polyunsaturated TGs with double bonds at 5, 7, 12, and 14 displayed significant variation between the wild type and two mutants. Our study is the first to reveal that the changes in the LPS structure of C. sakazakii resulted in altered lipid profiles and intensities, which may be a critical biochemical basis for bacterial resistance to harsh stresses.